Collaboration between Journalism and Academia: Projects, trends and hybridizations of a necessary synergy - Vaquerizo Domínguez, Enrique (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Traditionally, academics have played roles within the media limited as experts, collaborators or qualified sources. With the development of new communication platforms and the greater multidisciplinary conception of media teams, the presence of academics in the production and dissemination of journalistic content has gradually become normalized. In this article we approach from several case studies the possibilities, challenges and productive dynamics that reflect several representative projects of collaboration between journalism and academia. The results consolidate the idea that academics help to increase the credibility of the media by producing verified and in-depth content in a period when citizens' distrust of journalism is growing.